2020
DOI: 10.1136/jitc-2020-000538
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of immune checkpoint inhibitors in advanced urological cancers with pre-existing autoimmune disorders: a retrospective international multicenter study

Abstract: BackgroundThere is limited experience regarding the safety and efficacy of checkpoint inhibitors (CPI) in patients with autoimmune disorders (AD) and advanced urological cancers as they are generally excluded from clinical trials due to risk of exacerbations.MethodsThis multicenter retrospective cohort analysis of patients with advanced renal cell cancer (RCC) and urothelial cancer (UC) with pre-existing AD treated with CPI catalogued the incidence of AD exacerbations, new immune-related adverse events (irAEs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…On the aspect of safety, Menzies et al ( 15 ) reported that flares occurred more often in patients with active AID than in those with inactive AID (60% versus 30%, p = 0.039), and there was a trend for more flares in patients on immunosuppression treatment than in those not on immunosuppression (50% versus 31%, p > 0.05). The study of Martinez Chanza et al ( 33 ) also reached a conclusion consistent with that of Menzies et al. Similarly, the study of Leonardi et al ( 31 ) suggested that AID was more likely to flare in patients with active symptoms, and Kähler et al ( 26 ) also reported that flares occurred more often in patients on immunosuppression at the start of treatment.…”
Section: Literature Experience With Icis In Aid Patientsmentioning
confidence: 58%
See 4 more Smart Citations
“…On the aspect of safety, Menzies et al ( 15 ) reported that flares occurred more often in patients with active AID than in those with inactive AID (60% versus 30%, p = 0.039), and there was a trend for more flares in patients on immunosuppression treatment than in those not on immunosuppression (50% versus 31%, p > 0.05). The study of Martinez Chanza et al ( 33 ) also reached a conclusion consistent with that of Menzies et al. Similarly, the study of Leonardi et al ( 31 ) suggested that AID was more likely to flare in patients with active symptoms, and Kähler et al ( 26 ) also reported that flares occurred more often in patients on immunosuppression at the start of treatment.…”
Section: Literature Experience With Icis In Aid Patientsmentioning
confidence: 58%
“…Therefore, patients with those AIDs may be under-represented in the retrospective studies. Many studies yielded similar conclusions ( 15 , 26 29 , 31 , 33 36 , 38 ). That is, preexisting rheumatologic AIDs (such as RA, polymyalgia rheumatica) and Ps were most likely to effect AID flare after ICI therapy (the incidences of AID flare were 50% to 68% and 20% to 67% in patients with rheumatologic AIDs and Ps, respectively).…”
Section: Literature Experience With Icis In Aid Patientsmentioning
confidence: 70%
See 3 more Smart Citations